Projeto político-pedagógico: análise do referencial teórico produzido após o período de 1990 - Batista, Keila Cristina (2012)
This work was carried out aiming at analyzing the theoretical produced from the 1990s period in the field of educational research about the Political-Pedagogical Project in order to identify which is the design of PPP expressed by researchers who have been addressing this issue; what difficulties they point in the production process of the project and the reflections they present on the limits of its production facing the educational policies implemented, especially since the 1990s, and thus on the economic, political and ideological context when it is produced. The study is organized into three chapters. In the first chapter, entitled "The Political and Ideological Context in which the Process of Preparing the Political-Pedagogical Project Emerges", we discuss the process of democratization of Brazilian society in the 1980s, aspects of democratization, the process of democratization of education from proposals organized by the Forum for Education in the Assembly in Defense of Public and Free Education, the enactment of the Federal Constitution of 1988 and the Law of Guidelines and Bases of National Education no. 9394/96, documents which highlight principles related to democratic governance and the development and implementation of pedagogical proposals. Then we focus on the assumptions of neo-liberalism and elements of the ideology of postmodernism, which reflect the assumptions that support the reforms implemented in the 1990s. In the second chapter, our main concern is to present the concept of Political-Pedagogical Project, the difficulties and limitations mentioned by the authors regarding the document. In the third chapter, guided by the light of the considerations set out in previous chapters, our intention was to develop a theoretical analysis produced from 1990 about the PPP trying to check whether the concept of PPP as a document of responsibility of the school is the result of how this project is treated in theoretical work that addresses this issue and determine whether such concept incorporates elements present in theoretical liberalism, State reform and the ideology of post-modernism. In the final considerations, within the limits of the study, we recovered aspects that we consider fundamental for reflection on the theoretical work concerning the Political-Pedagogical Project.